Interações entre nanocristais semicondutores de CdTe e complexos polipiridínicos de rutênio (ll) - Bispo, Thalita Santos (2016)
In this work Ru(II) polypyridine complexes were used as redox active molecules to study interactions with quantum dots (QDs) surface. The synthesis of cadmium telluride (CdTe) quantum dots passivated with the organic stabilizer mercaptopropionic acid (MPA) and with stabilizer mixture of MPA and L-cysteine (CYS) was carried out in aqueous solution via hydrothermal heating, and the synthesis parameters such as pH and Cd/Te/stabilizer ratio were fixed according to the literature. The colloidal dispersion was characterized by UV visible absorption spectroscopy, as well as infrared and photoluminescence. Absorption spectra were broad with a single band and the emission showed band maxima at 612 nm and 598 nm for CdTe-MPA and CdTe-MPA/CYS (labelled in this work as CdTe-CYS) respectively (indicating quantum confinement). Particle diameters were calculated using a cubic empirical formula based on the maximum absorption wavelength. Cyclic voltammetry showed the presence of anodic and cathodic peaks corresponding to redox processes of CdTe QDs. Electrochemical band gaps were estimated from the onset values of oxidation and reduction peaks, finding a correspondence with the optical band gaps estimated from absorption and emission spectra. Polypyridine ruthenium(II) complexes [Ru(bpy)3](PF6)2 and [Ru(Me-bpy)3](PF6)2 (labelled in this work as Ru-1 and Ru-2, respectively) were synthesized via hydrothermal method for 72 h at 170ºC. The solids obtained were characterized by UV visible spectroscopy and the main transitions involved in the polypyrinde complexes were observed. Fluorescence spectroscopy exhibited a band assigned to the radiative deactivation of the lowest energy excited state (3MLTC). A redox pair of the complex was observed in the cyclic voltammograms, assigned to Ru2+/Ru3+ metal center. The possibility of interactions between the quantum dots and the complexes was evaluated by electrochemical measurements. Anodic differential pulse voltammograms showed that the redox potentials of QDs were modified due to the presence of the Ru(II) polypyridine complexes onto the QD’s surfaces. Oxidation peak from QDs was shifted to more positive values while the complexes’s redox peaks shifted to less positive values, indicating that the system shows characteristics of a nanocrystal molecular conjugated.